2019
DOI: 10.1161/circresaha.118.314240
|View full text |Cite
|
Sign up to set email alerts
|

Circ_Lrp6, a Circular RNA Enriched in Vascular Smooth Muscle Cells, Acts as a Sponge Regulating miRNA-145 Function

Abstract: Rationale: microRNAs (miRNAs) modulate gene expression by repressing translation of targeted genes. Previous work has established a role for miRNAs in regulating vascular smooth muscle cell (VSMC) activity. Whether circular RNAs are involved in the modulation of miRNA activity in VSMCs is unknown. Objective: We aimed to identify circular RNAs interacting with miRNAs enriched in VSMCs and modulating the cells’ act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(121 citation statements)
references
References 63 publications
2
119
0
Order By: Relevance
“…Just 1 year later, simultaneously published by two groups, 3,12 circRNA CDR1as was shown to act as a competing RNA molecule by sponging miRNAs. Shortly afterward, several other circRNAs were reported and shown to act as miRNA sponges also, [61][62][63][64][65][66][67] strengthening the general miRNA sponge function of circRNAs. However, most circRNAs do not contain multiple miRNA-binding sites, 13 thus miRNA sponging is just one of multiple potential functions.…”
Section: Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Just 1 year later, simultaneously published by two groups, 3,12 circRNA CDR1as was shown to act as a competing RNA molecule by sponging miRNAs. Shortly afterward, several other circRNAs were reported and shown to act as miRNA sponges also, [61][62][63][64][65][66][67] strengthening the general miRNA sponge function of circRNAs. However, most circRNAs do not contain multiple miRNA-binding sites, 13 thus miRNA sponging is just one of multiple potential functions.…”
Section: Detectionmentioning
confidence: 99%
“…68 Subsequent to the cdr1as publications in 2013, multiple other circR-NAs were shown to act as miRNA sponges. [61][62][63][64][65][66][67] Using bioinformatics tools, miRNA-binding sites can be predicted within the circRNA sequence (e.g., by using CircInteractome 55 ). Therefore, circRNAs that hold conspicuous many miRNA-binding sites for the same miRNA can be relatively easily uncovered as miRNA sponges.…”
Section: Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has indicated that the abnormal expression of miRNAs serves an important role in transplanted vascular diseases and they have received much interest in the research of various diseases (21,(45)(46)(47). Proliferation, migration and phenotypic transformation of SMcs or endothelial cells are associated with various miRNAs (48) including miR-145 (49,50), miR-222 (51), miR-195 (52) and miR-21 (53). For example, Liu et al (54) confirmed that the upregulation of miR-378a targeted cyclin-dependent kinase 1 to promote the proliferation and migration of vascular SMcs and increase the incidence of in-stent restenosis following stenting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have shown that circ_Lrp6 regulated the proliferation and migration of VSMCs by sponging miR-145. 9 More importantly, circRNAs also participated in modulating cell fates in VMSCs under hypoxic conditions. For instance, silencing of circ_000595 decreased hypoxia-induced VSMCs apoptosis by augmenting miR-19a, which has been shown to arrest the cell cycle by impeding cyclinD1 expression.…”
mentioning
confidence: 99%